Growth patterns of preterm and small for gestational age children during the first 10 years of life - Nguyen, Phuong Thi; Nguyen, Phuong Hong; Tran, Lan Mai; Khuong, Long Quynh; Nguyen, Son Van; Young, Melissa F.; Ramakrishnan, Usha (Frontiers Media, 2024)
Background: Preterm and small for gestational age (SGA) remain significant public health concerns worldwide. Yet limited evidence exists on their growth patterns during childhood from low-or middle-income countries.